48 clues into the disappearance of my sister ebook - Oates, Joyce Carol (2023)
A CrimeReads, AARP, Los Angeles Magazine and Dayton Daily News "Most Anticipated" Release In the newest literary thriller from celebrated author Joyce Carol Oates, a woman mysteriously vanishes, leaving her sister behind to tally up the clues and discover her fate. What has become of Marguerite Fulmer? On an otherwise average day in Upstate New York, the young woman left her family home, never to return. No note was left, no explanation; just a messy bedroom and her sister Gigi, driven to dig through the meager clues and discover the truth behind her disappearance. As the investigation unfolds, every subtle bit of evidence becomes a potential clue. The silk Dior slip dress, left in a heap on the floor; the impression of Ferragamo boots outside in the dirt, a trail of footsteps that abruptly ends before it leaves the yard. And as Gigi trails the detectives, she finds previously unknown troubles in the life of her perfect, gorgeous, much-loved sister?troubles that at times seem to reflect her own. Bit by bit, like ripping the petals off a flower blossom, a dark truth is revealed. And subtly, but with the unbearable suspense at which Joyce Carol Oates excels, clues mount and bring to light the fate of the missing beauty.